(untitled) (Mongolian Journal of Chemistry, 2020)
This research studied proximate, phytochemical and antioxidant properties of Diodia sarmentosa leaves. The ethanol and aqueous extracts of the leaves significantly inhibited 2,2-diphenyl-1-picrylhydrazyl (DPPHo) radical formation with IC50 values of 10.994 and 10.121 μg/mL respectively, compared to the ascorbic acid standard (IC50 value = 17.916 μg/mL). The aqueous extract exhibited more inhibitory effect on thiobarbituric acid-reactive species (TBARS) with IC50 values of 2.657 μg/mL while the ethanol extract had an IC50 value of 8.53 μg/mL compared to butylated hydroxytoluene standard (IC50 = 2.142 μg/mL). For the total antioxidant capacity assay, the aqueous extract had higher ascorbic acid equivalent values than the ethanol extract. However, the two solvent extracts showed antioxidant activity. Diodia sarmentosa leaves possess useful phytochemicals which are indicative of its antioxidant properties.